2015
DOI: 10.5194/acp-15-10965-2015
|View full text |Cite
|
Sign up to set email alerts
|

Ozone and NO<sub><i>x</i></sub> chemistry in the eastern US: evaluation of CMAQ/CB05 with satellite (OMI) data

Abstract: Abstract. Regulatory air quality models, such as the Community Multiscale Air Quality model (CMAQ), are used by federal and state agencies to guide policy decisions that determine how to best achieve adherence with National Ambient Air Quality Standards for surface ozone. We use observations of ozone and its important precursor NO2 to test the representation of the photochemistry and emission of ozone precursors within CMAQ. Observations of tropospheric column NO2 from the Ozone Monitoring Instrument (OMI), re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 73 publications
3
57
1
Order By: Relevance
“…In general, AM3 overestimates surface MDA8 ozone in both years by about 16 ppb on average, with NMB of 33-45 % and NME of 35-46 %. This positive bias of summertime surface ozone has been a common issue in a number of modeling studies of this region (Fiore et al, 2009;Canty et al, 2015;Brown-Steiner et al, 2015;Strode et al, 2015;Travis et al, 2016). This might be partially attributed to overestimated anthropogenic NO x emissions from nonpower plant sectors, excessive vertical mixing in the boundary layer , or underestimates of ozone dry deposition (Hardacre et al, 2015;Val Martin et al, 2014).…”
Section: Surface Ozonementioning
confidence: 99%
“…In general, AM3 overestimates surface MDA8 ozone in both years by about 16 ppb on average, with NMB of 33-45 % and NME of 35-46 %. This positive bias of summertime surface ozone has been a common issue in a number of modeling studies of this region (Fiore et al, 2009;Canty et al, 2015;Brown-Steiner et al, 2015;Strode et al, 2015;Travis et al, 2016). This might be partially attributed to overestimated anthropogenic NO x emissions from nonpower plant sectors, excessive vertical mixing in the boundary layer , or underestimates of ozone dry deposition (Hardacre et al, 2015;Val Martin et al, 2014).…”
Section: Surface Ozonementioning
confidence: 99%
“…MEGAN computes emissions based on emission source types and their densities, ambient carbon dioxide (CO 2 ) concentrations, and meteorological conditions (e.g., temperature, solar radiation, and moisture). It has been found that the MEGAN emissions are often higher than those calculated using other emission models, and are possibly associated with positive biases (e.g., Millet et al, 2008;Warneke et al, 2010;Carlton and Baker, 2011;Canty et al, 2015;Hogrefe et al, 2011;Emmerson et al, 2016). These biases, which still need careful validation with observationbased emission fluxes, can pose significant difficulties to accurately simulating isoprene and secondary air pollutants by chemical transport models.…”
Section: Introductionmentioning
confidence: 99%
“…Global CTMs typically have a horizontal resolution of 2-5 • . Meanwhile, high-resolution simulations have been conducted using regional models, which have shown the ability to simulate observed high tropospheric NO 2 columns over major polluted regions such as East Asia, North America, and Europe (e.g., Uno et al, 2007;Kim et al, 2009;Huijnen et al, 2010a;Itahashi et al, 2014;Yamaji et al, 2014;Canty et al, 2015;Han et al, 2015;Harkey et al, 2015). High-resolution simulations can lead to improvements in two ways: (1) through reduced spatial representation gaps between observed and simulated fields and (2) via improved representation of large-scale concentration fields through a consideration of small-scale processes.…”
Section: Introductionmentioning
confidence: 99%